Good Character and Philosophy in Plato's Republic - MacNeill, Rod (My University, 2020)
In this thesis, I argue that the ethical theory Plato develops in the Republic assigns critical importance to the role of one’s moral dispositions in their ability to make progress in philosophy. On this view, cultivating a good character, although not sufficient for pursuing philosophy, is necessary for success in philosophic endeavor. Conversely, having a vicious character precludes one from being able to acquire wisdom, which is the goal of philosophy. This is in contrast to Socratic intellectualism, which Plato is commonly seen to have adhered to in his earlier writings. The intellectualist view holds that knowledge is sufficient for virtue, and so one naturally becomes virtuous through the acquisition of wisdom. In other words, rather than virtuous character being necessary for philosophy, it is merely an effect of becoming wise. I argue that Plato moderates this kind of intellectualism in Republic in a way that makes the relationship between moral virtue and wisdom bidirectional. I demonstrate the plausibility of this thesis by examining an array of themes in the Republic, starting with the nature of philosophy and what it means to be a philosopher, and concluding with a look at the theory of education Plato advances throughout the dialogue.
Keywords: Philosophy; Ancient Philosophy; Ethics; Virtue; Plato; Republic